ANALISIS PERUNTUKAN DANAU SIPIN DITINJAU DARI KETERSEDIAAN DAN KUALITAS AIR - Guntar Marolop S; Sutrisno Sutrisno (Jurnal Civronlit Unbari, 2017)
The Lake is an ecosystem of wetlands to note preserved. However, since the Lake is an open system that can also be utilized for the certain provisions tailored to support power and capacity of the Lake. One of the supported power and capacity of the Lake is the availability and quality of the water of the Lake. Sipin lakes located in the city of Jambi, have long been exploited by various parties, just that its utilization is not maximal for a variety of activities. To maximize its utility it is necessary to know the power support and power tampungnya. By knowing the power support and power tampungnya then it can be determined the allocation it is used so that will give you maximum results. One of the variables that need to be taken care of in order to use Sipin Lake against correspond to peruntukkannya is about the availability and quality of water. Study on quantity and quality of water of the Lake can be done by way of Sipin analyzed the data using the method of precipitation F.J. Mock. Water quality studies done by using water quality Index method of electronically Stored. F.J. method using Mock data to analyze rainfall from year 2005 until 2015, obtained that debit maximum inlet reach 4,870 m3/sec and the minimum discharge of 2,090 m3/sec.Method Stored i.e. testing kualiats Sipin lake water from year 2014 2016 disimpulkkan s/d that the water quality of Lake Sipin only in accordance with the requirements of the water quality of the IV. From fluctuations in discharge and water quality of the IV, then Lake peruntukaan Sipin can only be utilized to provide water gardening or urban businesses or other businesses that comply with the requirements of the water quality of the IV.Keywords: Lake, water quantity, water quality, allocation, and utilization.